The effect of variable pay schemes on workplace absenteeism - Konstantinos Pouliakas; Nikolaos Theodoropoulos (Institute for the Study of Labor (IZA), 2011)
We estimate the effect of variable pay schemes on workplace absenteeism using two cross sections of British establishments. Private sector establishments that explicitly link pay with individual performance are found to have significantly lower absence rates. This effect is stronger for establishments that offer variable pay schemes to a greater share of their non-managerial workforce. Matched employer-employee data suggest that the effect is robust to a number of sensitivity tests. We also find that firms that tie a greater proportion of employees' earnings to variable pay schemes are also found to experience lower absence rates. Further, quintile regression results suggest that variable pay schemes have a stronger effect on establishments with an absence rate that is higher than an average or sustainable level. Finally, panel data suggest that a feedback mechanism is present, whereby high absenteeism in the past is related to a greater future incidence of individual variable pay schemes, which, in turn, is correlated with lower absence rates.
urn:nbn:de:101:1-201109286348
Keywords: J22; J33; C21; 330; performance-related pay; absenteeism; incentives; Britain; Leistungsentgelt; Fehlzeit; Ökonomischer Anreiz; Großbritannien